2019
DOI: 10.1080/01639625.2019.1624101
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Convenience: Determinants of White-Collar Crime Intention

Abstract: This file was downloaded from BI Open, the institutional repository (open access) at BI Norwegian Business School https://biopen.bi.no.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…With regards to the objective of revealing the most frequently encountered themes, our review shows that the phenomenon of deviance is explained grounded on the classical theories. The researchers choose between explanatory theories such as: differential association, routine activities and opportunities theories, social learning, social control, social disorganization, anomie and strain theories, subcultural theories, power relations, and neutralization and deterrence theories (Benda and Corwyn, 1997;Wagner et al, 2004;Wallace et al, 2007;Dolliver and Rocker, 2017;Meldrum et al, 2020), or socio-constructionist -symbolic interactionism, labeling theory, phenomenological theory, critical discourse analysis, cultural theories, framing theory, convenience theory, and postmodernist theories (Giordano et al, 2009;Herman-Kinney and Kinney, 2013;Gottschalk, 2018Gottschalk, , 2020Barmaki, 2021) or even the integrative ones, respectively social disorganization theory and life-course theories (Apel and Sweeten, 2010;Peguero, 2011;Payne and Welch, 2016;Gostjev and Nielsen, 2017). Consequently, our review showed that most of the analyzed studies centered on the predictors and correlates of deviance.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the objective of revealing the most frequently encountered themes, our review shows that the phenomenon of deviance is explained grounded on the classical theories. The researchers choose between explanatory theories such as: differential association, routine activities and opportunities theories, social learning, social control, social disorganization, anomie and strain theories, subcultural theories, power relations, and neutralization and deterrence theories (Benda and Corwyn, 1997;Wagner et al, 2004;Wallace et al, 2007;Dolliver and Rocker, 2017;Meldrum et al, 2020), or socio-constructionist -symbolic interactionism, labeling theory, phenomenological theory, critical discourse analysis, cultural theories, framing theory, convenience theory, and postmodernist theories (Giordano et al, 2009;Herman-Kinney and Kinney, 2013;Gottschalk, 2018Gottschalk, , 2020Barmaki, 2021) or even the integrative ones, respectively social disorganization theory and life-course theories (Apel and Sweeten, 2010;Peguero, 2011;Payne and Welch, 2016;Gostjev and Nielsen, 2017). Consequently, our review showed that most of the analyzed studies centered on the predictors and correlates of deviance.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, existentialist theory posits that meaning maintenance or actualization operates to affirm, enable, or justify action, thus realizing authenticity (Proulx, 2013 ; van Tilburg & Igou, 2011 ). Authenticity or actualization to follow or realize the meaning of activity in life has activated youth behavior, including delinquency and violence (Gottschalk, 2020 ; Ribeaud & Eisner, 2015 ; Shen et al, 2012 ; Walters, 2021 ). According to existentialist theory, such realization is a cause of crime, as associated with radicalism (B.…”
Section: Relating Radicalism and Life Meaningfulnessmentioning
confidence: 99%
“…The criminological literature: Since the seminal studies of Sutherland (1941Sutherland ( , 1945 into the crimes of entrepreneurs and the business community, the literature on so-called white-collar criminality (Sutherland, 1945;Croall, 1989Croall, , 2010Gottschalk and Asting, 2019;Gottschalk, 2020) has burgeoned into a siloed subliterature of its own. Bradshaw (2006) argued that the white-collar and criminal businessmen are in effect wolves in sheep's clothing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, white-collar criminality has become subsumed into the literature of business crime, which covers a wide gamut of criminality from crimes committed by businessmen such as tax evasion, embezzlement and frauds to predatory crimes such as theft, kidnapping, armed robbery and protection rackets committed on the business community by the established criminal fraternity. In the literature, the businessman is viewed as the “victim” or bad apple and much of the literature does not take cognisance of the agency of the criminal business to commit crime simply because it is convenient and financially beneficial to do so (see Gottschalk, 2020; Coxhead, 2022). Tilly and Hopkins (2008) argue that the businessman is both victim and villain in that they often under report crimes against their businesses and pragmatically tolerate criminal predation as simply part of doing business and stress that some businessmen may also participate in fencing/resetting stolen property because they have the capital to do so.…”
Section: Introductionmentioning
confidence: 99%